Neonatal classic galactosemia-diagnosis, clinical profile and molecular characteristics in unscreened Turkish population - Celik, Muhittin; Akdeniz, Osman; Ozbek, Mehmet Nuri; Kirbiyik, Ozgur (Oxford Univ Press, 2022)
Background Classic galactosemia (CG) is a rare hereditary disease that can cause serious morbidity and death if it is not diagnosed and treated in early periods of life. Clinical findings usually occur in the neonatal period after the neonate is fed with milk that contains galactose. Most patients are presented with jaundice, hepatomegaly, hypoglycemia and cataracts. Objective We aimed to document the clinical, molecular characteristics, regional estimated incidence and time of diagnosis in newborn with CG. Materials and method The data of 63 newborn with CG who were diagnosed and followed up between January 2011 and January 2018 were analyzed retrospectively. Results During the study period, 63 (33 boys and 30 girls) newborns were diagnosed with CG. The median gestational age was 39 weeks (33-42). Major presenting symptoms were jaundice 90.5% and cataract 41.2%. The mean age at first symptom was 12 +/- 7.4 days while the mean age at diagnosis was 18.9 +/- 10.6 days. Nearly half of the patients (55.5%) were diagnosed later than the postnatal 15th day. Genetic analysis was performed on 56 patients and homozygous Q188R mutation was found in 92.8%. There were signs of sepsis in 33.3% of the cases. Six patients died due to sepsis. There was consanguinity in 84.1% of the parents and regional estimated incidence was calculated as 1 in 6103 live births. Conclusion Q188R mutation was found in 92.8% of our cases. The regional estimated incidence was found as 1 in 6103 live births. Our study strongly supports that galactosemia should be included in the national newborn screening program.
Keywords: classic galactosemia; galactose-1-phosphate uridyl transferase; incidence; newborn